DETEKSI DINI DAN PENANGANAN DISLEKSIA: STUDI KASUS PADA ANAK USIA DINI DI SPS TAAM NURUL HIDAYAH - Sumiati, Ucu; Rifdatul Hidayah, Tazkia; Irma Suryani, Ade; Aliyani, Nuni; Anggraeni, Ira (LPPM Universitas Bina Bangsa, 2025)
This study aims to explore the process of early detection and treatment of dyslexia in early childhood at SPS TAAM NURUL HIDAYAH. Dyslexia is a disorder in reading ability that can hinder a child's academic achievement and social development, even though the child has normal intelligence. The research was conducted using a qualitative approach through in-depth interviews with two teachers in class A and direct observation of the learning process, to obtain a comprehensive picture of the challenges faced in detecting and managing dyslexia. Data were analyzed thematically to identify the main patterns and themes that emerged in the detection and intervention practices implemented. The results showed that most teachers still rely on general observations without any systematic measurement tools to detect early signs of dyslexia. However, there were efforts to use multisensory learning methods and simple technological aids to support the learning process of children with reading difficulties. However, limitations in the provision of specific intervention materials and lack of in-depth training for educators are obstacles in optimizing the treatment of dyslexia. Therefore, increasing teacher awareness and competence in the field of early detection and treatment of dyslexia is needed so that the interventions carried out can support children's academic and social development to the fullest.